Meat and heme iron intake and esophageal adenocarcinoma in the European Prospective Investigation into Cancer and Nutrition study. Issue 11 (6th July 2013) - Jakszyn, Paula; Luján‐Barroso, Leila; Agudo, Antonio; Bueno‐de‐Mesquita, H. Bas; Molina, Esther; Sánchez, Mª José; Fonseca‐Nunes, Ana; Siersema, Peter D; Matiello, Amalia; Tumino, Rosario; Saieva, Calogero; Pala, Valeria; et al.
Abstract : Although recent studies suggest that high intakes of meat and heme iron are risk factors for several types of cancer, studies in relation to esophageal adenocarcinoma (EAC) are scarce. Previous results in the European Prospective Investigation into Cancer and Nutrition (EPIC) based on a relatively small number of cases suggested a positive association between processed meat and EAC. In this study, we investigate the association between intake of different types of meats and heme iron intake and EAC risk in a larger number of cases from EPIC. The study included 481, 419 individuals and 137 incident cases of EAC that occurred during an average of 11 years of follow‐up. Dietary intake of meat (unprocessed/processed red and white meat) was assessed by validated center‐specific questionnaires. Heme iron was calculated as a type‐specific percentage of the total iron content in meat. After adjusting for relevant confounders, we observed a statistically significant positive association of EAC risk with heme iron and processed meat intake, with HR: 1.67, 95% CI: 1.05–2.68 and HR: 2.27, 95% CI:1.33–3.89, respectively, for comparison of the highest vs . lowest tertile of intake. Our results suggest a potential association between higher intakes of processed meat and heme iron and risk of EAC. Abstract : What's new? Previous results have shown that eating red meat can increase one's risk of developing certain cancers, including esophageal adenocarcinoma (EAC). That work included few cases of EAC, however. This study expands on those findings by investigating the effect of eating different kinds of meats and includes a larger number of esophageal cancer cases. Using a questionnaire, they assessed the amount of processed and unprocessed red or white meat consumed by individuals, including 137 EAC patients. They also estimated the amount of heme iron consumed based on the amount and types of meat eaten by the study subject. The analysis shows that consumption of processed meat and heme iron appear to be associated with higher risk of esophageal adenocarcinoma.